Nongkrong as a Form of Stress Coping among Teenagers in Makassar City - Dyan Paramitha Darmayanti (Universitas Negeri Makassar, 2024)
Nongkrong is a term often used in Indonesia to describe casual gathering and socialising, usually in public places such as cafes, food stalls or parks. It has become an integral part of the lifestyle of young Indonesians, especially among teenagers. The purpose of this study is to explore the role of nongkrong as a way to deal with stress among adolescents in Makassar City. Qualitative research methods were used by conducting in-depth interviews, participatory observation, and thematic analysis to understand how nongkrong can help reduce stress and improve emotional well-being. The results showed that nongkrong provides important social support, allowing adolescents to share their experiences and feelings in a relaxed and supportive environment. The social interactions that occur while nongkrong help reduce academic and social pressures while improving social and emotional abilities. However, this study also highlights the negative impacts of nongkrong such as disruption to study time as well as the risk of being influenced by negative peer behaviour. Therefore, it is important for adolescents to be selective in their choice of friends and manage their time wisely. Therefore, it is important for adolescents to be selective in their choice of friends and manage their time wisely. Overall, nongkrong can be an effective way for adolescents to deal with stress as long as it is done wisely and in a positive environment. Support from family and educational institutions is needed to help adolescents manage stress with healthy and constructive strategies. This study provides new insights into cultural stress management practices among university students in Indonesia.